Does Mindfulness Foster Grit in Young Learners? Evidence from Islamic Primary Schools across Sociodemographic Contexts - Santy Andrianie; Arifah Wulandari; Elwas Berdha Krismona; Zaida Nor Zainudin; Nor Zaiham Midawati Abdullah; Khairul Bariyyah; Mayobi Aluzo Putra (IJECA (International Journal of Education and Curriculum Application), 2026)
This study investigates whether mindfulness fosters grit among Islamic elementary school students across diverse socio-demographic contexts in Indonesia. The growing need for non-cognitive competencies, such as perseverance and self-regulation, underscores the importance of identifying psychological factors that support students’ academic persistence. Therefore, this research aims to examine the predictive role of mindfulness for grit and explore variations in both constructs by gender, residential area (rural–urban), and province. A quantitative cross-sectional design was employed involving 535 students from Islamic primary schools across 24 provinces. Data were collected using adapted versions of the Child and Adolescent Mindfulness Measure and an elementary school grit scale, both demonstrating acceptable validity and internal consistency reliability in the Indonesian context. Statistical analyses included descriptive statistics, independent samples t-tests, one-way ANOVA, and simple linear regression. Results indicate that most students demonstrate moderate levels of mindfulness and grit, with significant differences across gender, region, and province. Female and rural students score higher on mindfulness and grit. Regression analysis reveals that mindfulness significantly predicts grit (β = 0.440, p < .001), explaining 19.4% of the variance, suggesting that present moment awareness and emotional regulation contribute to students’ perseverance. These findings imply that cultivating mindfulness within Islamic educational settings may strengthen character education and enhance academic resilience. Future research should use longitudinal and experimental designs, include multi-informant data, and consider contextual factors to better understand how mindfulness supports grit development.